Development of a Core Outcome Measure Instrument; "LeishCOM_LCL", for Localised Cutaneous Leishmaniasis. - Shalindra Ranasinghe; Sujai Senarathne; Vijani Somaratne; Charles J N Lacey; Surangi Jayakody; Amila Wickramasinghe; Indira Kahawita; Hiro Goto; Mitali Chatterjee; José A L Lindoso; Vivak Parkash; Surya J Chaudhuri; et al. (PLoS Neglected Tropical Diseases)
Background Localized cutaneous leishmaniasis (LCL) is a chronic ulcerating disease. A literature review identified inconsistencies in clinical trials. The aims of this study were to reach a consensus on the most important domains to measure when assessing LCL, agree on parameters to measure the domains, and develop a tool representing a Core Outcome Set (COS), for use in clinical assessment of LCL. Methodology & principal findings A literature review was conducted to identify any existing COS for LCL embracing agreed Outcome Domains, i.e. what to measure and any Outcome Measurement Instruments (OMIs). As no COS was available, potential outcome domains for assessment of LCL were identified through an international collaborative approach using e-consultations and virtual discussions with expert stakeholders (n = 20) from geographically different LCL endemic countries. Subsequent judgmental validation process included a face-to-face multidisciplinary stakeholders' meeting adopting the Nominal Group Technique. A final consensual agreement on outcome domains and items required to measure these domains was established. "Clinical Cure" was defined as the ideal overall "General Concept". The five Core Outcome Domains included Signs capturing clinical morphology, diameter, and induration of an index lesion with the aid of a palpability score, Treatment Efficacy assessing percentage change in size of the lesion and re-epithelialization compared to baseline, Treatment Impact which included an investigator and patient visual analogue score, and Clinical Sequelae rating pigment change, atrophic and hypertrophic/keloid scars. It was agreed that two open-ended questions should be included to capture some aspects of Health-Related Quality of Life as a means of capturing a patient-focused approach. Conclusion LeishCOM_LCL was generated to reflect a COS for LCL. This captured demographic details, agreed outcome domains and measures to assess these domains. Validation of LeishCOM_LCL will be reported in a separate paper. Development of a Patient Reported Outcome Measure will be considered in the future.